Introduction to fiber optics and telecommunications - Costa, Manuel F. M. (2008)
The evolution of technology and the development of new solutions that directly affects our everyday life demand the establishment of a sound scientific and technological literacy in our societies. From early ages our youngsters and pupils should have an enduring and efficient knowledge update especially in what concerns key proficiency and aptitudes. It is so important to promote the pedagogical conception development and production of new materials and equipment that may allow the introduction, in-school but also in informal learning environments, to basic concepts of recently developed high-tech including the underlying scientific theories. In our days, in our Information (or better Knowledge based) Society, telecommunications play a fundamental, crucial, role. With the massive increase of the amount of information that needs to be exchange, virtually in real time, between all the points of the globe, all the telecommunications system had to be redesigned and renewed in the last decades. At present, optical fibers are at the foundation of all modern telecommunications system. It was its sprouting and development which allowed telecommunications development to the level that we now observe and to what is already foreseen in a near future. Thus optical fibers and waveguides are surely our day’s one of the most important domains of physics and of Science and Technology in general.